Diagnostic Accuracy of Increased Endometrial Thickness on Transvaginal Ultrasound in Predicting Uterine Pathology in Postmenopausal Bleeding (Medical Forum Monthly, 2024)
Objective: To assess the precision of transvaginal ultrasound in identifying endometrial pathology in patients presenting with postmenopausal bleeding, using endometrial thickness >4mm, taking histopathology as the standard diagnostic tool.Study Design: Descriptive cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology, Lahore Medical and Dental College/Ghurki Trust Hospital, Lahore from 28th July 2021 to 27th January 2022.Methods: Fifty women aged 45-75 years with postmenopausal bleeding were included, while patients with other pathologies, bleeding disorders, or those taking hormone therapy were excluded. Endometrial thickness was measured via transvaginal ultrasound, followed by hysteroscopy and biopsy for histopathological evaluation.Results: There were 22 cases as true positive, 2 were false positive, whereas 2 cases were found false negative, and 24 found to be true negative (P=0.0001). Accordingly, the performance indicators of a diagnostic test i.e., sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of transvaginal ultrasound were computed as 91.67%, 92.31%, 91.67%, 92.31%, and 92.0%, respectively.Conclusion: Transvaginal ultrasound demonstrates diagnostic accuracy of high degree for prognosticating uterine pathology in patients with postmenopausal bleeding and can be an effective non-invasive diagnostic tool to rule out endometrial malignancy.